THE EFFECT OF USING DISCUSSION METHOD IN STUDENTS’ SPEAKING ABILITY AT THE TENTH GRADE STUDENTS OF SMK SWASTA HKBP PEMATANGSIANTAR - ROHDEARNI WATI SIPAYUNG (LP2MTBM MAKARIOZ, 2019)
This study is focus on the effect of using discussion method in students’ speaking abilility at the tenth grade students of SMK Swasta HKBP Pematangsiantar. According to Schmuck, Discussion Method is a strategy for achieving instructional objectives that involves a group of persons, usually in the roles of moderator and participant, who communicate with each other using speaking, nonverbal, and listening processes.The populations in this study are 80 students of 3 classes. The choosing of sample is done by using purposive sampling thus gotten the sample as big as 52 students ( 2 classses)The data analysis is done by counting the Mean (????̅) and the Standart Deviation (S) and the hypothesis will be proved by testing the significant of coleration statistic students or testing-t . The Mean of Pre Test Experimen Class is 3,78 and the Mean of Post Test Experiment Class is 8,05. The Mean of Pre Test Control Class is 3,74 and the Mean of Post Test Control Class is 6,55.The testing of hypothesis for pre test between experiment class and control class is gotten ????ℎ????????????????????(2,45 ) < ???????????????????????? (7,14). So ????0 is received and ???????? is rejected, it means that there is any effect of using discussion method in students’ speaking ability.